ANALISA KONDISI KERUSAKAN JALAN MENGGUNAKAN METODE PAVEMENT CONDITION INDEX - Muhammad Ridha; Meliyana Meliyana (Universitas Teuku Umar, 2019)
The Kaye Lhon road section of Teunom Aceh Jaya Subdistrict is the main route that connects Banda Aceh City with districts in the West Coast region which is a national road with the function as the primary collector road that is passed most by various types of vehicles as a result the main roads are in sections the road is no longer able to serve the existing traffic flow properly, as long as the crossing is very prone to accidents because some road conditions are damaged. Based on the condition of the damaged road, the researchers used the PCI (Pavement Condition Index) method to see the conditions of the pavement when surveying the road with STA 191 + 000 to 193 + 00 for 2000 meters and divided into 10 sample unit segments. Each sample unit is evaluated by measuring dimensions, identifying types and levels of damage to obtain PCI values. The analysis showed that the damage was cracked by alligator cracks 50% of the total damage area of 1,067.95 m2, weathering and loose grain 30% of the total damage area of 631.42 m2, utility excavation 12% of total damage area 251.37 m2, corrugated (4) total damage area 83.40 m2, holes (potholes), 2% total damage area 52.93 m2, grooves (rutting) 1% total damage area 11.97 m2, and collapse (depression) 1% of the total damage area of 11.87 m2. The average PCI value on the Jalan Kaye Lhon section of Teunom Aceh Jaya Subdistrict in kilometer 191 to 193 is 42.30 which is categorized as Fair (fair), so it needs a serious handling from the government to mmediately make repairs before the damage becomes more severe.